Rapid engineering and re-configuration of automation objects aided by formal modelling and verification. (1st February 2007) - Vyatkin, Valeriy; Hanisch, Hans-Michael; Karras, Sirko; Pfeiffer, Thomas; , Victor Dubinin
This paper is about the engineering of the information processing and control part of intelligent manufacturing systems. A number of recently developed technologies can bring qualitative benefits to the users and vendors of such systems. In particular, component distributed architectures (IEC 61499), mechatronic ontologies, object-oriented design methods (UML) and formal verification, if properly combined, can provide real plug and play of intelligent machines, and thus drastically improve the flexibility of manufacturing systems. The paper surveys important relevant works in the area of intelligent automation and presents new ideas on object-oriented development of automation systems. The ideas presented in this paper reflect current progress of the ongoing R&D project VAIAS, 'Validatable Architectures for Industrial Automation Systems'.